The development of prejudice in children : The case of Cyprus - Ioannou, Maria; Kassianos, Angelos P. (My University, 2018)
In this chapter, we discuss the concept of prejudice, broadly defined as a generalized antipathy toward a social group (Allport 1954), and how it develops in children through the lens of different developmental theories. We use these theoretical foundations to examine the case of Cyprus in relation to prejudice development among Greek and Turkish Cypriot children. In the first part of the chapter, we discuss concepts adjacent to prejudice such as category awareness, identification with one’s own category, preference for one’s own social group, and discrimination against other social groups, and we present the key social psychological theories of prejudice development in children. The second part of the chapter is devoted to presenting the case of Cyprus as a context of ethnic conflict and inter-ethnic prejudice. We review the main studies aiming to track the onset as well as the nature of prejudice among Greek and Turkish Cypriot children and critically discuss these studies while highlighting the specificities of the Cypriot sociopolitical context. In the last part of the chapter, we discuss how existing theories of prejudice development can not only inform the case of Cyprus but can also be informed by it. We conclude by offering a set of recommendations about addressing prejudice in childhood through research and education.